PENGARUH GLOBALISASI TERHADAP EKSISTENSI SEDEKAH BUMI PADA MASYARAKAT SUNDA PEKON MERBAU - Rahayu, Sri; Adha, Muhammad Mona; Putri, Devi Sutrisno (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2022)
The existence of Sedekah Bumi has decreased due to globalization. This has become a problem in Pekon Merbau in the social and cultural fields, such as the loss of the original culture of an area such as Sedekah Bumi. The current of globalization has had a major influence on Indonesian culture, including the Sedekah Bumi ceremony. The rapid pace of information and telecommunications can actually lead to a tendency that leads to the waning of the value of cultural preservation. Therefore, this research was conducted with the aim of knowing the influence of globalization on the existence of the Sedekah Bumi tradition in society. The research method used is a quantitative approach with descriptive methods, then data collection techniques in the field are carried out by means of observation and questionnaires. Based on the results of the study indicate that globalization affects the existence of the Sedekah Bumi in Pekon Merbau. This is shown from the results of the simple linear regression analysis test showing the t-count value of 3.136 and the sig value of 0.002. Thus it can be concluded that t hitung > t table is 3.136 > 0.67581 and the value of sig < 0.05 is 0.002 < 0.05 so that H0 is rejected and H1 is accepted. Globalization is a factor that can affect the fading of the existence of the Sedekah Bumi in Pekon Merbau, so that if globalization is positive, the influence will be positive on the existence of the Sedekah Bumi which indicates that the Sedekah Bumi tradition will increasingly fade. On the other hand, if globalization is negative, the impact will be negative, which means the Sedekah Bumi tradition will be stronger and continue to be preserved.Keywords: Sedekah Bumi, Globalization, Existence